2016
DOI: 10.1590/0100-69912016003007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of ventilatory function through pre and postoperative peak expiratory flow in patients submitted to elective upper abdominal surgery

Abstract: Objective: to evaluate the ventilatory function by Peak Expiratory Flow (PEF) in the immediate pre and postoperative periods of patients undergoing elective surgical procedures in the upper abdomen. Methods: we conducted a prospective cohort study including 47 patients admitted to the Hospital Regional de Mato Grosso do Sul from July to December 2014, who underwent elective surgeries of the upper abdomen, and submiited to spirometric evaluation and measurement of PEF immediately before and after surgery. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
1
6
0
1
Order By: Relevance
“…Postoperatively, the peak of diaphragmatic dysfunction occurs in the period between two and eight hours after surgery, returning to preoperative values in roughly seven to ten days (5) . A study that The type of surgery performed in the patients in this study may cause changes in the diaphragmatic respiratory pattern, which usually makes breathing shallower with thoracic predominance, which may explain the alteration in the "depth of breath" indicator identified in this sample.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Postoperatively, the peak of diaphragmatic dysfunction occurs in the period between two and eight hours after surgery, returning to preoperative values in roughly seven to ten days (5) . A study that The type of surgery performed in the patients in this study may cause changes in the diaphragmatic respiratory pattern, which usually makes breathing shallower with thoracic predominance, which may explain the alteration in the "depth of breath" indicator identified in this sample.…”
Section: Discussionmentioning
confidence: 96%
“…Respiratory changes that occur in the postoperative period can result in severe complications, affecting about 25-50% of patients undergoing major surgical procedures. The literature indicates that the surgical site is the most important factor for determination of postoperative pulmonary complications (POPC), which occur in 10-40% of the cases of patients whose surgical incision is in the upper abdomen or in the thorax (5) . A study (16) that investigated the occurrence of POPC identified that thoracic (28.9%), cardiac (28%) and upper abdominal (24.3%) surgery had the highest complication rates in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations